Split-appendix technique for simultaneous use in the mitrofanoff principle and posterior urethral substitution in a bladder exstrophy–epispadias complex patient - Yogesh Kumar Sarin; Parveen Kumar (Journal of Indian Association of Pediatric Surgeons, 2019)
We describe the case of a bladder exstrophy–epispadias complex (BEEC), in which a “split” appendix was used simultaneously as a posterior urethral replacement (for strictured Mitchell's repair) as well as a Mitrofanoff channel. Split appendix had been used before for simultaneous Mitrofanoff and Malone's antegrade contrast enema channels to manage neurogenic bladder and bowel. To the best of our knowledge, this is the first reported case for the use of split appendix for urethral reconstruction in a child with BEEC.